Discrete element simulation of the grain mixing law in brown rice germination device - Yan, Jiagang; Xie, Biao; Bai, Jinyin; Zheng, Yun; Zhao, Shibo; Liu, Nian; Zhang, Qiang (International Journal of Agricultural and Biological Engineering, 2024)
The discrete element method (DEM) was used in this study to numerically simulate the mixing process and motion law of particles in brown rice germination device. And the reliability of simulation experiments was verified through physical experiments. In the discrete element simulation experiment, there were three mixing stages in the mixing process of the particles. The particle motion conditions at different rotational speeds were rolling, cascading, cataracting and centrifuging. The lower the filling degree, the higher the particle mixing efficiency. The radial trajectory of the particles was approximated as an elliptical helix that continuously shrank towards the axis. The research results indicated that under the same speed and filling conditions, the motion of brown rice particles in both the simulated and physical test environments is rolling and the drop height is the same. Keywords: brown rice germination device tank, brown rice particles, discrete element method, motion law, mixing characteristics DOI: 10.25165/j.ijabe.20241701.8014 Citation: Yan J G, Biao X, Bai J Y, Zheng Y, Zhao S B, Liu N, et al. Discrete element simulation of the grain mixing law in brown rice germination device. Int J Agric & Biol Eng, 2024; 17(1): 41-48.